Integrated Polarity Optimization of MPRM Circuits Based on Improved Multi‐objective Particle Swarm Optimization. Issue 5 (1st September 2020) - Fu, Qiang; Wang, Pengjun; Tong, Nan; Wang, Mingbo; Zhong, Caiming
Abstract : Aiming at the multi‐objective polarity design of Mixed‐polarity Reed‐Muller (MPRM) circuit, such as small area and low power consumption, an integrated polarity optimization scheme based on improved Multi‐objective particle swarm optimization (MOPSO) is proposed. In the Improved MOPSO (IMOPSO) algorithm, particles in the external archive can be actively evolved through self‐learning operations to find better circuit polarity. The particles in the population achieve selflearning fractals by comparing the differences between their own states and individuals in external archive to enhance the evolutionary level of the population. A multiobjective decision model of area and power consumption is established according to the characteristics of MPRM circuit. The tabular technique and the IMPOPO algorithm are combined to obtain the Pareto optimal polarity set of the MPRM circuit for area and power consumption. The MCNC Benchmark circuit is used to test the performance of the algorithm. The results verify the effectiveness of the proposed algorithm.